Harnessing the efficacy of multifunctional rhizobacterial consortia for promoting the growth of Anethum graveolens L. - Joshi, Nishra; Saraf, Meenu; Jha, Chaitanya Kumar; Sudha, A.; Alharbi, Sulaiman Ali; Alfarraj, Saleh; Datta, Rahul (Frontiers in Sustainable Food Systems, 2023)
Co-cultures of bacteria are more metabolically flexible and more tolerant to changes in the environment than single cultures. In order to test for plant growth promotion in a medicinal herb Anethumgraveolens L, potent phosphate-solubilizing rhizobacteria were selected, characterized and assessed for compatibility with each other.Molecular identification of isolates was made by 16s rRNA sequence,and they were identified as Pseudomonas aeruginosaNJC4 (OP289324), Serratia marcescens NJC21(OP289323) and Bacillusspp. Dual species consortia,namely, Bacillus spp. + Serratia marcescens NJC21 (T1), and Pseudomonas aeruginosa NJC4 + Serratia marcescens NJC21 (T2), were tested for their ability to produce multiple plant beneficial activities such as phosphate solubilization, and ammonia and indole acetic acid production. The best isolate and consortium were evaluated for plant growth promotion activity. A plant treated with consortia T-2 seemed most effective in seed emergence at 84.66%, which was four times superior to the control. Growth and yield characters, along with all different rhizobacterial treatments, were examined by principal component analysis (PCA), where PC1 can explain 51.37% of the total variance and PC2 can explain 26.75%. PC1 was associated with wet biomass, chlorophyll b, and total chlorophyll content, which reflect the strong influence of consortia T-1. At the same time, PC2 was found to be related to dry biomass and chlorophyll a content. This study lends credence to the theory that microbial consortiums consisting of more than one efficient strains may be more effective than single cultures in boosting the increase of agricultural output in a sustainable way.